Circular RNA CEP128 acts as a sponge of miR-145-5p in promoting the bladder cancer progression via regulating SOX11 - Zhun Wu; Wei Huang; Xuegang Wang; Tao Wang; Yuedong Chen; Bin Chen; Rongfu Liu; Peide Bai; Jinchun Xing (BMC, 2018)
Abstract Background This study aimed to investigate the effect of over-expressing circular RNA CEP128 (circCEP128) on cell functions and explore the molecular mechanism of which in bladder carcinoma. Methods The differentially expressed circRNAs and mRNAs in bladder carcinoma cells and cells in adjacent tissues were screened out using microarray analysis. Expression levels of circRNAs and mRNAs in tissues and cells were determined by qRT-PCR. Expression of SOX11 was detected by western blot. Luciferase reporter assay and RNA pull-down assay were used to investigate the interactions between the specific circRNA, miRNA and mRNA. Cell cycle and apoptosis were measured using flow cytometry after transfection. MTT assay was also performed to detect the cell proliferation. Results In present study, circCEP128 and SOX11 were observed significantly up-regulated in bladder cancer tissues, while the expression of miR-145-5p was decreased in cancer samples compared to normal samples. Cytoscape was used to visualize circCEP128-miRNA-target gene interactions based on the TargetScan and circular RNA interactome, which revealed that circCEP128 served as a sponge of miR-145-5p and indirectly regulated SOX11. Knockdown of circCEP128 induced the inhibition of cell proliferation and the increased bladder cancer cell apoptosis rate. Conclusions CircCEP128 functions as a ceRNA for miR-145-5p, which could up regulates SOX11 and further promotes cell proliferation and inhibits cell apoptosis of bladder cancer.